New insight of the pathogenesis in osteoarthritis: the intricate interplay of ferroptosis and autophagy mediated by mitophagy/chaperone-mediated autophagy - An, Fangyu; Zhang, Jie; Gao, Peng; Xiao, Zhipan; Chang, Weirong; Song, Jiayi; Wang, Yujie; Ma, Haizhen; Zhang, Rui; Chen, Zhendong; Yan, Chunlu (Frontiers in Cell and Developmental Biology, 2023)
Ferroptosis, characterized by iron accumulation and lipid peroxidation, is a form of iron-driven cell death. Mitophagy is a type of selective autophagy, where degradation of damaged mitochondria is the key mechanism for maintaining mitochondrial homeostasis. Additionally, Chaperone-mediated autophagy (CMA) is a biological process that transports individual cytoplasmic proteins to lysosomes for degradation through companion molecules such as heat shock proteins. Research has demonstrated the involvement of ferroptosis, mitophagy, and CMA in the pathological progression of Osteoarthritis (OA). Furthermore, research has indicated a significant correlation between alterations in the expression of reactive oxygen species (ROS), adenosine monophosphate (AMP)-activated protein kinase (AMPK), and hypoxia-inducible factors (HIFs) and the occurrence of OA, particularly in relation to ferroptosis and mitophagy. In light of these findings, our study aims to assess the regulatory functions of ferroptosis and mitophagy/CMA in the pathogenesis of OA. Additionally, we propose a mechanism of crosstalk between ferroptosis and mitophagy, while also examining potential pharmacological interventions for targeted therapy in OA. Ultimately, our research endeavors to offer novel insights and directions for the prevention and treatment of OA.